Bad magic - Bosch, Pseudonymous (New York : Little, Brown and Company, 2014)
"Thirteen-year-old Clay, a boy who no longer believes in magic, tags graffiti on his classroom wall and, as punishment, is sent to a camp for wayward kids located on a volcanic island, where eccentric campmates abound, a ghost walks among the abandoned ruins of a mansion, and a dangerous force threatens to erupt with bad magic."--Provided by publisher.
Keywords: Camps -- Juvenile fiction; Fantasy fiction